Mexico : Arrangement Under the Flexible Credit Line and Cancellation of the Current Arrangement-Staff Report; Staff Supplement; and Press Release on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2012)
The report discusses the important role of the Flexible Credit Line (FCL) in helping Mexico to survive in the fragile global economic environment. The FCL's contribution in maintaining an orderly financial market in Mexico is noteworthy. IMF staff reaffirms their commitment toward Mexico in taking the necessary actions to manage unforeseen risks. According to the IMF staff report, Mexico meets the qualification criteria for access to FCL resources, and staff recommends approval of a fund of SDR 47.292 billion for a period of 24 months.